Identification of key design parameters for earthquake resistance of reinforced concrete shell structures - Michiels, Tim; Adriaenssens, Sigrid (Engineering structures, 2017)
•The factors determining the earthquake resistance of reinforced concrete shells are investigated.•Vibrational properties and displacement and stress response to earthquake loading is analyzed.•Singly curved and doubly curved shells with square plan of 20 m by 20 m and thickness of 8 cm are considered.•It is shown that shells with high fundamental frequency perform superior under earthquake loading.•Furthermore, shells with small to medium span can be intrinsically earthquake resistant. Concrete roof shells have shown to be inherently able to sustain earthquakes, but the reasons for this apparent seismic resistance have been subject to limited research. Concrete shells exhibit a high structural efficiency and thus can be constructed very thin. Because of their relative lightweight nature, the earthquake forces induced in a thin shell structure are relatively low. However, the shape of a shell structure is typically established so that it performs optimally under gravity loads, carrying the loads to the foundations mainly through membrane action over the shell surface. Unanticipated horizontal forces induced by earthquakes generate bending stresses in concrete shell structures, which could lead to structural damage. Through a parametric study of 8 cm thick, concrete roof shells with a square plan, the research presented in this paper demonstrates that small to mid-sized (span<15 m) thin concrete roof shells can indeed be intrinsically earthquake resistant. They owe this resistance to their great geometric stiffness and low mass, which lead to high fundamental frequencies that are well above the driving frequencies of realistic seismic actions. Due to these characteristics the shells analyzed in this paper behave elastically under the earthquake excitation, without surpassing the maximum allowable concrete strength. For shallow shells it is observed that the vertical components of the earthquake vibrations, can induce larger stresses in the shell than the horizontal components. It is further demonstrated that by increasing the rise and curvature of larger shells (20 m by 20 m), their fundamental frequencies are increased and the damaging effect of the vertical earthquake vibration components mitigated.